PELAKSANAAN UPACARA ADAT PERKAWINAN MASYARAKAT MELAYU DI DESA KAPUAS RAYA KECAMATAN BUNUT HILIR KABUPATEN KAPUAS HULU - NIM. A1012191004, DIMAS ANGGRA SAPUTRA (Fakultas Hukum Universitas Tanjungpura, 2022)
Abstrac The implementation of the Malay Community Traditional Marriage Ceremony in Kapuas Raya Village, Bunut Hilir District, Kapuas Hulu Regency is a manifestation of the Malay Indigenous People and their belief in their ancestors and ancestors. In the social life of the Malay Indigenous People in Kapuas Raya Village, they adhere to the provisions of customary law as a guideline for attitude and behavior that covers the whole of life, meaning that it includes marriage. Marriage has an important meaning for the Malay Indigenous People in Kapuas Raya Village, not only to get offspring but also as an important thing to do. The procedure for carrying out the traditional Malay marriage ceremony in Kapuas Raya Village is divided into two, namely before the Marriage Agreement and after the Marriage Agreement which includes: Mission (Introduction Period), Bepintak (Asking), Besurung (Engaged), Mutual Cooperation, Berzanzi ( Reading of the Holy Qur'an verses Bestep (Dance), Beaci (Besolek), after the Marriage Agreement includes: Marriage Agreement (Ijab Qabul), Fresh Flour (Congratulations Prayer), Safe Bathing (Bathing for Safety), and Amik Main (Visiting Husband's House). In its implementation, it underwent several shifts from its original form, which underwent a shift, namely the implementation of Bestep or Dancing and Besurung or Engagement.The formulation of the problem in this research is